POTENTIAL ABILITY OF THE SOLANUM-FEEDING LADYBIRD BEETLE HENOSEPILACHNA DIFFINIS (COLEOPTERA; COCCINELLIDAE) TO USE THE INTRODUCED FABACEOUS PLANT CENTROSEMA MOLLE - Kikuta, Shogo; Fujiyama, Naoyuki; Kahono, Sih; Kobayashi, Norio; Hartini, Sri; Katakura, Haruo (TREUBIA, 2013)
Host specificity has been a major factor in generating the tremendous diversity of phytophagous arthropods. Studies of adaptation to introduced or invasive plant species provide an opportunity to investigate incipient evolutionary changes in host specificity. We investigated the cryptic ability of the Asian tropical herbivorous ladybird beetle Henosepilachna diffinis to feed on the fabaceous weed "centro", Centrosema molle, which was introduced to Southeast Asia about 200 years ago. In laboratory choice tests using this plant and the normal host plant, Solanum torvum, adults preferred S. torvum to centro, but over half the beetles tested ate leaves of both plants. Furthermore, most first-instar larvae accepted centro during a rearing experiment, and a few of them grew to the third-instar stage, though none reached the final (fourth) instar. Henosepilachna diffinis likely acquired this incomplete acceptability of centro without any direct host-grazer interaction with centro, probably before this weed was introduced to Southeast Asia. Our results further suggest that another Henosepilachna species, H. vigintioctopunctata, might similarly have already acquired an incomplete ability to use centro when this beetle encountered it for the first time, and this triggered a subsequent host-range expansion from solanaceous plants to include centro in various parts of Southeast Asia.